A liquid crystal spinning method for heterocyclic aramid fibers

By using twin-screw polymerization reactor and dry spray wet spinning process in the production of heterocyclic aramid fibers, combined with neutralization treatment of weak alkali aqueous solution, the problems of poor mechanical properties and high production costs in traditional processes are solved, and the problem of poor fiber mechanical properties and high production costs in traditional processes is achieved. High performance and efficient production of heterocyclic aramid fibers.

CN119162686BActive Publication Date: 2025-02-14YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411649146.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The production process of traditional heterocyclic aramid fibers has problems such as poor stability of polymer stock solution, poor mechanical properties of fibers and high production costs.

Method used

The polymerization reaction was carried out by a twin-screw polymerization reactor, and heterocyclic aramid fibers were prepared by dry spray wet spinning process, and neutralized with weak alkali aqueous solution to improve the mechanical properties of the fibers.

Benefits of technology

The tensile strength, elastic modulus and decomposition temperature of heterocyclic aramid fiber are improved, the mechanical properties and production efficiency of the fiber are enhanced, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_31
    Figure SMS_31
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of aramid production, and specifically to a liquid crystal spinning method for heterocyclic aramid fiber, wherein the spinning method is as follows: S1, preparation of heterocyclic aramid polymer powder: diamine monomer, third monomer and terephthaloyl chloride are subjected to polymerization reaction in a twin-screw polymerization reactor, and after the reaction, the powder is neutralized, ground, washed and dried with an alkaline substance to obtain a heterocyclic aramid polymer powder; S2, preparation of heterocyclic aramid fiber: the heterocyclic aramid polymer powder is dissolved, filtered and degassed with concentrated sulfuric acid to obtain a liquid crystal spinning solution, and then subjected to a dry-jet wet spinning process: spinning, coagulation molding, washing, neutralization, washing, drying and heat drawing to obtain the heterocyclic aramid fiber; the neutralizer used in the neutralization process of step S2 is a weak alkali aqueous solution. The heterocyclic aramid fiber obtained by the spinning method of the present invention has higher mechanical properties, less lint and good softness, and can meet the application requirements of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a liquid crystal spinning method for heterocyclic aramid fibers, belonging to the technical field of aramid production. Background Art

[0002] Para-aramid fiber has excellent properties such as high strength, high modulus, and high temperature resistance, and has important applications in civilian fields such as tires, bulletproof vests, fire retardant, and cut resistance. However, for applications with higher performance requirements, such as aircraft engines and rocket shells, traditional para-aramid cannot meet the application requirements.

[0003] Heterocyclic aramid (also known as aramid III in China) is an organic fiber with higher strength, higher modulus and higher temperature resistance than traditional para-aramid. Its tensile strength can reach up to 5.0 Gpa, elastic modulus can reach 150 GPa, and decomposition temperature can reach 560 ℃. Heterocyclic aramid is the main material for preparing rocket engine shells, bulletproof vests, tanks, composite armor, high-strength cables and other products. Traditionally, heterocyclic aramid is made of terephthaloyl chloride, p-phenylenediamine and benzimidazole diamine as raw materials. In polar solvent N,N-dimethylacetamide containing cosolvents (such as calcium chloride, lithium chloride, etc.), low-temperature solution polymerization is carried out to prepare copolymers. The polymer mother liquor is wet-spun to obtain heterocyclic aramid fibers.

[0004] Typical brands of heterocyclic aramid fibers include: SVM, Aroms, Rusar NT, etc. At present, the tensile strength of heterocyclic aramid fibers can reach up to 5.2 GPa. The preparation of aramid III fibers with higher strength and higher modulus requires high resin viscosity, fewer gel particles, and narrow molecular weight distribution. Russian patent applications RU2130980C1 and RU2074182C1 introduce the production technology of such resins and fibers. China Bluestar, Sichuan Huiteng, Guangzhou Caiyan and the 46th Institute of Aerospace Science and Industry have carried out research and development of heterocyclic aramid earlier. Chinese patents CN101781813B, CN101921395B, CN1480479B, CN101787582B, CN104357939B, CN101787582B, CN115678004B, etc. introduce low-temperature solution polymerization and wet spinning related processes of heterocyclic aramid. However, the current production process of heterocyclic aramid is based on direct wet spinning of unneutralized polymer stock solution. If the hydrochloric acid produced during the polymerization process is not neutralized, it will not only cause the degradation of polymer macromolecules, but also lead to poor batch stability of polymer powder and fiber, and serious hairiness; long-term use of unneutralized stock solution will also cause adverse effects such as corrosion to spinning equipment, increasing production costs and equipment depreciation costs. In addition, compared with the wet spinning process, the dry-jet wet spinning process has more advantages. First, the intrinsic viscosity of the polymer can be made higher, and the molecular weight of the polymer can be larger, so that the mechanical properties of the fiber are higher. Secondly, when concentrated sulfuric acid is used for liquid crystal spinning, the mass fraction of the spinning solution is much greater than the mass fraction of the stock solution during wet spinning, thereby reducing production costs. Third, from the perspective of production efficiency, dry-jet wet spinning has faster spinning and higher production efficiency. However, the dry-jet wet spinning process requires concentrated sulfuric acid spinning, and the aromatic heterocyclic structural units in the heterocyclic aramid macromolecular chain will be protonated, which will prevent the hydrogen bond interaction between the fiber macromolecular chains, thereby causing the mechanical properties of the fiber to decrease. The limitations of these spinning methods will affect the performance indicators of heterocyclic aramid fibers. Therefore, it is of great value to develop a liquid crystal spinning method for heterocyclic aramid fibers and obtain heterocyclic aramid fibers with high performance indicators by improving the spinning method. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a liquid crystal spinning method for heterocyclic aramid fibers. The prepared heterocyclic aramid fibers have higher mechanical properties, simple process and convenient operation.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: a liquid crystal spinning method for heterocyclic aramid fibers, the spinning method comprising:

[0007] S1. Preparation of heterocyclic aramid polymer powder:

[0008] The diamine monomer, the third monomer and terephthaloyl chloride are polymerized in a twin-screw polymerization reactor, and after the reaction is completed, the monomers are neutralized with an alkaline substance, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder;

[0009] The diamine monomer includes one or two of p-phenylenediamine and substituted p-phenylenediamine monomers, and the substituted p-phenylenediamine monomer is: ; Among them, R 1 , R 2 are independently selected from any one of F, Cl, Br, OCH3, and H, and R 1 , R 2 Not at the same time H;

[0010] The third monomer is selected from any one of the following structures:

[0011] ;

[0012] S2. Preparation of heterocyclic aramid fibers:

[0013] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, and then subjected to a dry-jet wet spinning process: spinning, coagulation, washing, neutralization, washing, drying, and heat drawing to obtain the heterocyclic aramid fiber; the neutralizing agent used in the neutralization process of step S2 is a weak alkaline aqueous solution.

[0014] Furthermore, in step S2, the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 15-35%, and the temperature of the liquid crystal spinning solution is 80-90°C.

[0015] Furthermore, during the spinning process of step S2, the air layer height of the liquid crystal spinning solution passing through the spinneret is 3-15 mm.

[0016] Furthermore, during the coagulation molding in step S2, the coagulation bath used is a sulfuric acid aqueous solution with a mass concentration of 10-30%, and the temperature of the coagulation bath is 20-30° C.;

[0017] In the water washing process of step S2, the water washing bath used is pure deionized water, and the water washing bath temperature is 20-40°C.

[0018] Furthermore, the neutralizing agent used in the neutralization process of step S2 is any one of a sodium carbonate aqueous solution, a sodium bicarbonate aqueous solution, a potassium carbonate aqueous solution, and a potassium bicarbonate aqueous solution, the mass concentration of the neutralizing agent is 5-20%, and the temperature of the neutralizing agent is 20-40°C.

[0019] Furthermore, the total draft ratio of the dry-jet wet spinning is 6.0 to 8.0 times.

[0020] Furthermore, the polymerization reaction operation process in step S1 is:

[0021] Under the protection of inert gas, the diamine monomer and the third monomer are dissolved in an amide solution containing a co-solvent, and transferred into a first twin-screw polymerization reactor; the temperature in the first twin-screw polymerization reactor system is controlled, and the first batch of terephthaloyl chloride is added to carry out the first batch of reaction;

[0022] After the first batch of reactions are completed, the reaction solution is cooled and sent to the second twin-screw polymerization reactor. The temperature in the second twin-screw polymerization reactor system is controlled, and the second batch of terephthaloyl chloride is added to carry out the second batch of reactions, and finally the polymerization reaction is completed.

[0023] Further, the molar ratio of the diamine monomer to the third monomer is 1:(0.5-3.5); the ratio of the total molar amount of the diamine monomer and the third monomer to the total molar amount of the terephthaloyl chloride is 1:(0.98-1.05);

[0024] The weight of the first batch of terephthaloyl chloride added is 40-50% of the total amount of terephthaloyl chloride added; the weight of the second batch of terephthaloyl chloride added is 50-60% of the total amount of terephthaloyl chloride added.

[0025] Furthermore, in step S1, the polymerization reaction temperature is -10~5°C.

[0026] Further, the substituted p-phenylenediamine monomer is selected from any one of the following structures:

[0027] .

[0028] The beneficial effects of the present invention are:

[0029] The polymerization process of the present invention adopts a twin-screw polymerization reactor. The intrinsic viscosity of the heterocyclic aramid polymer dry material prepared by a traditional kettle polymerization reactor is 4-6 dL / g. Due to the strong hydrogen bond interaction between the heterocyclic aramid macromolecular chains, when the polymerization reaction reaches a certain stage during the low-temperature solution polymerization process, the polymer will precipitate, thereby terminating the polymerization reaction. This will not only lead to relatively low intrinsic viscosity and molecular weight of the polymer, but also make the solid content of the polymer stock solution only about 6% at most. When this critical value is exceeded, the polymer will precipitate. When a twin-screw polymerization reactor is used, when the polymer precipitates from the solution system, due to the strong shearing effect of the twin-screw polymerization reactor, the solid phase-solid phase can still react, which not only overcomes the problem that the precipitation reaction of the heterocyclic aramid solution polymerization is easily terminated, thereby causing low solid content, but also makes the prepared polymer molecular weight and intrinsic viscosity higher, thereby making the mechanical properties of the fiber more excellent.

[0030] The present invention adopts a dry-jet wet-spinning spinning process to prepare heterocyclic aramid fibers. The wet spinning process widely used in the preparation of heterocyclic aramid fibers currently must use a polymer solution, and the disadvantages of the polymer solution will be further transferred to the wet spinning process. The wet spinning process not only has a slow spinning speed, but also requires further improvement in the quality of the fibers. The present invention uses a dry-jet wet-spinning process to obtain heterocyclic aramid fibers of better quality. After super-stretching in an air layer, the mechanical properties of the fibers are significantly improved compared to wet spinning. In addition, the spinning solution of the present invention has a higher mass fraction and a faster spinning speed, which will lead to an improvement in fiber production efficiency, thereby reducing production and operation costs.

[0031] The present invention adopts dry-jet wet spinning process to effectively solve the problem of incomplete acid removal in heterocyclic aramid fiber by conventional process. The acidic cations (H + ), which enhances the hydrogen bond interaction between the macromolecular chains in the fiber, and significantly improves the mechanical properties of the fiber.

[0032] In the spinning method of the present invention, the polymerization process and the spinning process conditions cooperate with each other, and the tensile strength and elastic modulus of the obtained heterocyclic aramid fiber are greatly improved compared with the currently commercially available heterocyclic aramid fiber prepared by the wet spinning process. The heterocyclic aramid fiber obtained by the spinning method of the present invention has a tensile strength of 5.6-6.4 GPa, an elongation at break of 3.1-5.2%, and an elastic modulus of 160-200 GPa. In addition, the heterocyclic aramid fiber obtained by the spinning method of the present invention has less fuzz and good softness, which can meet the higher performance requirements of aerospace for aramid fibers. DETAILED DESCRIPTION

[0033] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0035] A liquid crystal spinning method for heterocyclic aramid fibers, the spinning method comprising:

[0036] S1. Preparation of heterocyclic aramid polymer powder:

[0037] The diamine monomer, the third monomer and terephthaloyl chloride are polymerized in a twin-screw polymerization reactor, and after the reaction is completed, the monomers are neutralized with an alkaline substance, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder;

[0038] The diamine monomer includes one or two of p-phenylenediamine and substituted p-phenylenediamine monomers, and the substituted p-phenylenediamine monomer is: ; Among them, R 1 , R 2 are independently selected from any one of F, Cl, Br, OCH3, and H, and R 1 , R 2 Not at the same time H;

[0039] The third monomer is selected from any one of the following structures:

[0040] ;

[0041] S2. Preparation of heterocyclic aramid fibers:

[0042] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, and then subjected to a dry-jet wet spinning process: spinning, coagulation, washing, neutralization, washing, drying, and heat drawing to obtain the heterocyclic aramid fiber; the neutralizing agent used in the neutralization process of step S2 is a weak alkaline aqueous solution.

[0043] Specifically, in step S2, the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 15-35%, the temperature of the liquid crystal spinning solution is 80-90° C., and the mass concentration of the concentrated sulfuric acid is >99.8%.

[0044] Specifically, during the spinning process of step S2, the air layer height of the liquid crystal spinning solution passing through the spinneret is 3-15 mm.

[0045] Specifically, during the coagulation molding in step S2, the coagulation bath used is a sulfuric acid aqueous solution with a mass concentration of 10-30%, and the temperature of the coagulation bath is 20-30° C.;

[0046] In the water washing process of step S2, the water washing bath used is pure deionized water, and the water washing bath temperature is 20-40°C.

[0047] Specifically, the neutralizing agent used in the neutralization process of step S2 is any one of sodium carbonate aqueous solution, sodium bicarbonate aqueous solution, potassium carbonate aqueous solution, and potassium bicarbonate aqueous solution, the mass concentration of the neutralizing agent is 5-20%, and the temperature of the neutralizing agent is 20-40°C.

[0048] Specifically, the total draft ratio of the dry-jet wet spinning is 6.0 to 8.0 times.

[0049] Specifically, the polymerization reaction operation process in step S1 is:

[0050] Under the protection of inert gas, the diamine monomer and the third monomer are dissolved in an amide solution containing a co-solvent, and transferred into a first twin-screw polymerization reactor; the temperature in the first twin-screw polymerization reactor system is controlled, and the first batch of terephthaloyl chloride is added to carry out the first batch of reaction;

[0051] After the first batch of reactions are completed, the reaction solution is cooled and sent to the second twin-screw polymerization reactor. The temperature in the second twin-screw polymerization reactor system is controlled, and the second batch of terephthaloyl chloride is added to carry out the second batch of reactions, and finally the polymerization reaction is completed.

[0052] Specifically, the molar ratio of the diamine monomer to the third monomer is 1:(0.5-3.5); the ratio of the total molar amount of the diamine monomer and the third monomer to the total molar amount of the terephthaloyl chloride is 1:(0.98-1.05);

[0053] The weight of the first batch of terephthaloyl chloride added is 40-50% of the total amount of terephthaloyl chloride added; the weight of the second batch of terephthaloyl chloride added is 50-60% of the total amount of terephthaloyl chloride added.

[0054] Since the reaction between terephthaloyl chloride and p-phenylenediamine is a highly exothermic amidation reaction, it is necessary to control the intensity of the reaction by controlling the temperature and the amount of material added. The weight of the first batch of terephthaloyl chloride added is 40-50% of the total amount added; this can not only maintain a uniform solution system in the reaction system, but also prevent the polymer from precipitating in the reaction system; the weight of the second batch of terephthaloyl chloride added is 50-60% of the total amount added. At this time, the reaction system is no longer a solution system, but a solid-liquid mixed state. The polymer precipitates from the reaction system, and as the reaction proceeds, the reaction system eventually becomes a solid state.

[0055] Specifically, in step S1, the polymerization reaction temperature is -10~5°C.

[0056] Specifically, the substituted p-phenylenediamine monomer is selected from any one of the following structures:

[0057] .

[0058] More specifically, the amide solvent is N,N-dimethylacetamide or N-methylpyrrolidone, and the mass fraction of the co-solvent in the amide solvent is 0.5-5.5%.

[0059] More specifically, in step S1, the alkaline substance used in the neutralization operation is any one of sodium hydroxide, calcium hydroxide, potassium hydroxide, lithium hydroxide, diethylamine, ammonia, dimethylamine, methylamine, ethylamine, and propylamine.

[0060] More specifically, the structural formula of the heterocyclic aramid polymer is:

[0061] ; wherein Ar1 in the polymer is derived from a diamine monomer, and Ar2 is derived from a third monomer. m and n are positive integers, and the intrinsic viscosity of the heterocyclic aramid polymer powder at room temperature is 6.0-9.0 dL / g.

[0062] Take the following structural formula as an example to explain the specific principles involved in the coagulation and neutralization operations in the dry-jet wet spinning process:

[0063] .

[0064] Example 1

[0065] The diamine monomer of this embodiment 1 is: ;

[0066] The third monomer of this embodiment 1 is: ;

[0067] (1) Preparation of heterocyclic aramid polymer powder:

[0068] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, they are completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to the total amount of terephthaloyl chloride is 1:1.02;

[0069] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the mixture was cooled and transferred to the second twin-screw polymerization reactor.

[0070] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 8.0 dL / g.

[0071] (2) Preparation of heterocyclic aramid fibers:

[0072] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0073] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0074] Among them, the air layer height is 3cm, the coagulation bath composition is a 10% by mass dilute sulfuric acid aqueous solution, the temperature is 30℃; the water washing bath is water washing, the water washing bath is pure deionized water, the temperature is 30℃; the neutralization bath is a 5% sodium carbonate aqueous solution, the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 340℃ hot stretching process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0075] The total draft ratio of dry-jet wet spinning is 7.0 times.

[0076] Example 2

[0077] The diamine monomer of this embodiment 2 is: and ;

[0078] The third monomer of this embodiment 2 is: ;

[0079] (1) Preparation of heterocyclic aramid polymer powder:

[0080] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 1.0% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, they are completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:0.5, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:0.98;

[0081] The system temperature was controlled at 0°C, and 50% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the system was cooled and transferred to the second twin-screw polymerization reactor.

[0082] 50% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 15% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a characteristic viscosity of 7.5 dL / g.

[0083] (2) Preparation of heterocyclic aramid fibers:

[0084] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 15%, and the temperature of the liquid crystal spinning solution is 80°C.

[0085] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0086] Among them, the air layer height is 15cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 30%, and the temperature is 30℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 30℃; the neutralization bath is a 10% sodium carbonate aqueous solution, and the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 350℃ hot drawing process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0087] The total draft ratio of dry-jet wet spinning is 6.0 times.

[0088] Example 3

[0089] The diamine monomer of this embodiment 3 is: ;

[0090] The third monomer of this embodiment 3 is: ;

[0091] (1) Preparation of heterocyclic aramid polymer powder:

[0092] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 1.0% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, they are completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:3.5, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.05;

[0093] The system temperature was controlled at 5°C, and 45% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the reactor was cooled and transferred to the second twin-screw polymerization reactor.

[0094] 55% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a characteristic viscosity of 8.5 dL / g.

[0095] (2) Preparation of heterocyclic aramid fibers:

[0096] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 35%, and the temperature of the liquid crystal spinning solution is 90°C.

[0097] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0098] Among them, the air layer height is 10cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 20%, and the temperature is 25℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 25℃; the neutralization bath is a 10% sodium carbonate aqueous solution, and the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 360℃ hot stretching process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0099] The total draft ratio of dry-jet wet spinning is 8.0 times.

[0100] Example 4

[0101] The diamine monomer of this embodiment 4 is: ;

[0102] The third monomer of this embodiment 4 is: ;

[0103] (1) Preparation of heterocyclic aramid polymer powder:

[0104] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and sent to a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2.0, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.05;

[0105] The system temperature was controlled at -10°C, and 45% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the reactor was cooled and transferred to the second twin-screw polymerization reactor.

[0106] 55% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a characteristic viscosity of 8.2 dL / g.

[0107] (2) Preparation of heterocyclic aramid fibers:

[0108] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 20%, and the temperature of the liquid crystal spinning solution is 85°C.

[0109] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0110] Among them, the air layer height is 10cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 20%, and the temperature is 20℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 20℃; the neutralization bath is a 10% sodium carbonate aqueous solution, and the temperature is 30℃, and then after a 150℃ drying treatment, it enters a 350℃ hot drawing process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0111] The total draft ratio of dry-jet wet spinning is 8.0 times.

[0112] Example 5

[0113] The diamine monomer of this embodiment 5 is: and ;

[0114] The third monomer of this embodiment 5 is: ;

[0115] (1) Preparation of heterocyclic aramid polymer powder:

[0116] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 1.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and sent to a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2.0, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.05;

[0117] The system temperature was controlled at 0°C, and 45% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the system was transferred to the second twin-screw polymerization reactor after cooling.

[0118] 55% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 7.9 dL / g.

[0119] (2) Preparation of heterocyclic aramid fibers:

[0120] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 30%, and the temperature of the liquid crystal spinning solution is 85°C.

[0121] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0122] Among them, the air layer height is 10cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 20%, and the temperature is 25℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 40℃; the neutralization bath is a 20% sodium bicarbonate aqueous solution, and the temperature is 40℃, and then after a 150℃ drying treatment, it enters a 340℃ hot drawing process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0123] The total draft ratio of dry-jet wet spinning is 7.5 times.

[0124] Example 6

[0125] The diamine monomer of this embodiment 6 is: ;

[0126] The third monomer of this embodiment 6 is: ;

[0127] (1) Preparation of heterocyclic aramid polymer powder:

[0128] The substituted p-phenylenediamine monomer and the third monomer are added to an N-methylpyrrolidone solution containing 5.5% by mass of calcium chloride, stirred at 25°C for 1 hour under nitrogen protection, and completely dissolved, and then transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.03;

[0129] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the mixture was cooled and transferred to the second twin-screw polymerization reactor.

[0130] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 9.0 dL / g.

[0131] (2) Preparation of heterocyclic aramid fibers:

[0132] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0133] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0134] Among them, the air layer height is 9 cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 10%, and the temperature is 30°C; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 30°C; the neutralization bath is a 5% sodium carbonate aqueous solution, and the temperature is 20°C, and then after a 150°C drying treatment, it enters a 360°C hot stretching process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0135] The total draft ratio of dry-jet wet spinning is 7.5 times.

[0136] Comparative Example 1

[0137] The monomers used in this comparative example are the same as those in Example 1, except that a kettle polymerization reactor and a wet spinning process are used.

[0138] (1) Polymerization process:

[0139] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 3.5% lithium chloride by mass, and stirred at 25° C. for 1 hour under nitrogen protection until they are completely dissolved; the molar ratio of the substituted p-phenylenediamine monomer and the third monomer is 1:2, and the molar ratio of the total molar number of the substituted diamine monomer and the third monomer to terephthaloyl chloride is 1:1.05;

[0140] The system was cooled to 0°C, and then part of terephthaloyl chloride (94% of the total amount added) was slowly added within 150 minutes. The dynamic viscosity of the reaction was monitored to be 6.8 Po. Ammonia was introduced for neutralization, and the first step polymerization stock solution was obtained by filtration.

[0141] The remaining portion of terephthaloyl chloride (6% of the total amount added) was continued to be added to the first step polymerization stock solution, and diethylamine was added for neutralization to obtain a heterocyclic aramid polymer stock solution with a polymer solid content of 10.8% and a dynamic viscosity of 960 Po (25°C).

[0142] (2) Spinning process:

[0143] The heterocyclic aramid polymer stock solution is spun by a spinneret, formed by a coagulation bath, drawn by a drawing bath, washed by a water bath, dried, hot drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0144] Among them, coagulation bath molding: the coagulation bath composition is 45% by mass DMAc aqueous solution, the temperature is 30°C;

[0145] Drawing bath: The drawing bath composition is 30% DMAc aqueous solution, the temperature is 25 °C, and the drawing ratio in the drawing bath is 1.6 times;

[0146] Water washing: The water washing bath is pure deionized water at a temperature of 40°C; then it is dried at 150°C before entering the hot drawing process;

[0147] The thermal stretching adopts three-stage thermal stretching: the first-stage thermal stretching temperature is 255°C, and the first-stage thermal stretching ratio is 1.45 times; the second-stage thermal stretching temperature is 270°C, and the second-stage thermal stretching ratio is 1.15 times; the third-stage thermal stretching temperature is 310°C, and the third-stage thermal stretching ratio is 1.06 times.

[0148] The total draft ratio is 2.83 times.

[0149] Comparative Example 2

[0150] The monomers used in this comparative example are the same as those in Example 1, except that a kettle polymerization reactor process is used. In this comparative example 2, solids precipitate during the polymerization of the heterocyclic aramid polymer, and the polymerization process cannot proceed.

[0151] (1) Polymerization process:

[0152] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and stirred at 25° C. for 1 hour under nitrogen protection until they are completely dissolved; the molar ratio of the substituted p-phenylenediamine monomer and the third monomer is 1:2, and the molar ratio of the total molar number of the substituted diamine monomer and the third monomer to terephthaloyl chloride is 1:1.05;

[0153] The system was cooled to 0°C, and then part of terephthaloyl chloride (70% of the total amount added) was slowly added within 150 minutes. At this time, the polymer system solid precipitated and the polymerization process was terminated.

[0154] Comparative Example 3

[0155] The polymerization process in this comparative example is the same as that in Example 1, except that the spinning adopts a wet spinning process. The results show that the polymer powder obtained in the polymerization process cannot be dissolved in conventional solvents (such as DMAc, NMP) used in wet spinning, and the spinning process cannot be carried out.

[0156] Comparative Example 4

[0157] The monomers used in this comparative example are the same as those in Example 1, except that the base used in the neutralization process is a 5% sodium hydroxide solution.

[0158] The diamine monomer of this comparative example 4 is: ;

[0159] The third monomer of this comparative example 4 is: ;

[0160] (1) Preparation of heterocyclic aramid polymer powder:

[0161] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.02;

[0162] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the mixture was cooled and transferred to the second twin-screw polymerization reactor.

[0163] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 8.0 dL / g.

[0164] (2) Preparation of heterocyclic aramid fibers:

[0165] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0166] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0167] Among them, the air layer height is 3cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 10%, and the temperature is 30℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 30℃; the neutralization bath is a 5% sodium hydroxide aqueous solution, and the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 330℃ hot drawing process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0168] The total draft ratio of dry-jet wet spinning is 7.0 times.

[0169] Comparative Example 5

[0170] The monomers used in this comparative example are the same as those in Example 1, except that the base used in the neutralization process is a 5% potassium hydroxide solution.

[0171] The diamine monomer of this comparative example 5 is: ;

[0172] The third monomer of this comparative example 5 is: ;

[0173] (1) Preparation of heterocyclic aramid polymer powder:

[0174] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.02;

[0175] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the reactor was cooled and transferred to the second twin-screw polymerization reactor.

[0176] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 8.0 dL / g.

[0177] (2) Preparation of heterocyclic aramid fibers:

[0178] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0179] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0180] Among them, the air layer height is 3 cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 10%, and the temperature is 30°C; the water washing bath is water washing, and the water washing bath is pure deionized water at a temperature of 30°C; the neutralization bath is a 5% potassium hydroxide aqueous solution at a temperature of 20°C, and then after a drying treatment at 150°C, it enters a hot stretching process at 370°C; and the heterocyclic aramid fiber is obtained after oiling treatment.

[0181] The total draft ratio of dry-jet wet spinning is 7.0 times.

[0182] Comparative Example 6

[0183] The monomers used in this comparative example are the same as those in Example 1, except that the base used in the neutralization process is a 30% sodium carbonate solution.

[0184] The diamine monomer of this comparative example 6 is: ;

[0185] The third monomer of this comparative example 6 is: ;

[0186] (1) Preparation of heterocyclic aramid polymer powder:

[0187] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.02;

[0188] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the reactor was cooled and transferred to the second twin-screw polymerization reactor.

[0189] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 8.0 dL / g.

[0190] (2) Preparation of heterocyclic aramid fibers:

[0191] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0192] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0193] Among them, the air layer height is 3cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 10%, and the temperature is 30℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 30℃; the neutralization bath is a 30% sodium carbonate aqueous solution, and the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 340℃ hot drawing process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0194] The total draft ratio of dry-jet wet spinning is 7.0 times.

[0195] Comparative Example 7

[0196] The monomers used in this comparative example are the same as those in Example 1, except that the base used in the neutralization process is a 1% sodium carbonate solution.

[0197] The diamine monomer of this comparative example 7 is: ;

[0198] The third monomer of this comparative example 7 is: ;

[0199] (1) Preparation of heterocyclic aramid polymer powder:

[0200] The substituted p-phenylenediamine monomer and the third monomer are added to an N,N-dimethylacetamide solution containing 0.5% lithium chloride by mass, and after stirring at 25° C. for 1 hour under nitrogen protection, the mixture is completely dissolved and transferred into a twin-screw polymerization reactor; the molar ratio of the diamine monomer to the third monomer is 1:2, and the molar ratio of the total molar number of the diamine monomer and the third monomer to terephthaloyl chloride is 1:1.02;

[0201] The system temperature was controlled at 0°C, and 40% of terephthaloyl chloride was added in the first batch. After the reaction was completed, the reactor was cooled and transferred to the second twin-screw polymerization reactor.

[0202] 60% of terephthaloyl chloride was further added to the first step polymerization stock solution. After the reaction was completed, the solution was neutralized with a 5% by mass sodium hydroxide aqueous solution, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder having a polymer powder characteristic viscosity of 8.0 dL / g.

[0203] (2) Preparation of heterocyclic aramid fibers:

[0204] The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, and degassed to obtain a liquid crystal spinning solution, wherein the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 25%, and the temperature of the liquid crystal spinning solution is 85°C.

[0205] The liquid crystal spinning solution is spun by a spinneret, formed by a coagulation bath, washed, neutralized, washed, dried, hot-drawn, oiled and wound into a tube to obtain the heterocyclic aramid fiber;

[0206] Among them, the air layer height is 3cm, the coagulation bath composition is a dilute sulfuric acid solution with a mass fraction of 10%, and the temperature is 30℃; the water washing bath is water washing, and the water washing bath is pure deionized water, and the temperature is 30℃; the neutralization bath is a 1% sodium carbonate aqueous solution, and the temperature is 20℃, and then after a 150℃ drying treatment, it enters a 370℃ hot stretching process; after oiling treatment, the heterocyclic aramid fiber is obtained.

[0207] The total draft ratio of dry-jet wet spinning is 7.0 times.

[0208] The heterocyclic aramid fibers prepared in the above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1. The test method involved is: the test standard for fiber indicators GB / T 42823-2023, the test method: first weigh a certain amount of fiber filaments, test the linear density of the fibers, and then set the twist according to the linear density for twisting. Fix the twisted fibers on the tensile test fixture, measure the mechanical properties 10 times, and take the average. The electric stretching machine model is Instron 34TM-30.

[0209] Table 1 Heterocyclic aramid fiber performance test data

[0210]

[0211] It can be seen from the data in Table 1 above that the heterocyclic aramid fibers prepared by the preparation method of the present invention in Examples 1 to 6 have very good mechanical properties. The presence of a large number of strongly electronegative heteroatoms in the heterocyclic aramid fibers prepared by the spinning method of the present invention enhances the bonding force between the fibers and the epoxy resin.

[0212] From the data comparison of Example 1 and Comparative Example 1, it can be seen that the mechanical properties of the fiber using the process conditions of "twin screw polymerization + dry jet wet spinning" are better than those of "kettle polymerization + wet spinning". The molecular weight and intrinsic viscosity of the polymer can be made higher by using twin screw polymerization, and the mechanical properties of the fiber are significantly improved by the super-stretching of the air layer by dry jet wet spinning. + ) will hinder the hydrogen bond interaction between macromolecular chains, thereby weakening the mechanical properties of the fiber. The present invention removes the acidic cations (H + ), which enables the fibers to form hydrogen bonding interactions between macromolecular chains during the spinning process, which is beneficial to the improvement of the mechanical properties of the fibers.

[0213] From the comparison of the data of Example 1 and Comparative Example 2, it can be seen that in the solution polymerization in the kettle polymerization reactor, the content of the cosolvent is reduced, and the polymerization reaction is stopped to a certain extent, resulting in the precipitation of the polymer and the poor mechanical properties of the polymer. One of the advantages of the twin-screw polymerization reactor is the strong shearing effect between the screws, so that the polymer precipitated in the solution can continue to undergo polymerization reaction, thereby further improving the intrinsic viscosity and molecular weight of the polymer, and finally reaching the finished polymer powder.

[0214] From the comparison of the data of Example 1 and Comparative Example 3, it can be seen that: since the intrinsic viscosity and molecular weight of the polymer powder produced by the twin-screw polymerization reactor are very high, the polymer has poor solubility in the solvents (DMAc, NMP) used in conventional wet spinning, resulting in the inability to carry out the wet spinning process.

[0215] From the data comparison of Example 1 and Comparative Examples 4 and 5, it can be seen that when sodium hydroxide and potassium hydroxide with stronger alkalinity are used as neutralizers, the heterocyclic structural units in the fiber are unstable under strong alkaline conditions, and the five-membered heterocyclic ring will undergo a ring-opening reaction, thereby causing degradation of the fiber macromolecular chain and a decrease in the mechanical properties of the fiber.

[0216] From the data comparison of Example 1 and Comparative Examples 6 and 7, it can be seen that the concentration of weak alkali also has an important influence on the mechanical properties of the fiber. When the concentration is too high, the alkalinity of the neutralizing solution becomes stronger. Although the complexed hydrogen protons can be completely neutralized, it will also cause fiber degradation. When the concentration is too low, the hydrogen protons complexed by the heterocyclic structural units are not completely neutralized. In the subsequent hot drawing process, the hydrogen bond interaction between the macromolecular chains of the fiber is weakened, resulting in no obvious improvement in the mechanical properties of the fiber.

[0217] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0218] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A liquid crystal spinning method for heterocyclic aramid fibers, characterized in that: The spinning method is: S1. Preparation of heterocyclic aramid polymer powder: The diamine monomer, the third monomer and terephthaloyl chloride are polymerized in a twin-screw polymerization reactor, and after the reaction is completed, the monomers are neutralized with an alkaline substance, ground, washed with water and dried to obtain a heterocyclic aramid polymer powder; The diamine monomer includes one or two of p-phenylenediamine and substituted p-phenylenediamine monomers, and the substituted p-phenylenediamine monomer is: ; Among them, R 1 , R 2 are independently selected from any one of F, Cl, Br, OCH3, and H, and R 1 , R 2 Not at the same time H; The third monomer is selected from any one of the following structures: ; S2. Preparation of heterocyclic aramid fibers: The heterocyclic aramid polymer powder is dissolved in concentrated sulfuric acid, filtered, degassed to obtain a liquid crystal spinning solution, and then subjected to a dry-jet wet spinning process: spinning, coagulation, washing, neutralization, washing, drying, and heat drawing to obtain the heterocyclic aramid fiber; the neutralizing agent used in the neutralization process of step S2 is a weak alkaline aqueous solution; The polymerization reaction operation process described in step S1 is: Under the protection of inert gas, the diamine monomer and the third monomer are dissolved in an amide solution containing a co-solvent, and transferred into a first twin-screw polymerization reactor; the temperature in the first twin-screw polymerization reactor system is controlled, and the first batch of terephthaloyl chloride is added to carry out the first batch of reaction; After the first batch of reactions are completed, the reaction solution is cooled and sent to a second twin-screw polymerization reactor, the temperature in the second twin-screw polymerization reactor system is controlled, and a second batch of terephthaloyl chloride is added to carry out a second batch of reactions, and finally the polymerization reaction is completed; In step S1, the polymerization reaction temperature is -10~5°C; The neutralizing agent used in the neutralization process of step S2 is any one of a sodium carbonate aqueous solution, a sodium bicarbonate aqueous solution, a potassium carbonate aqueous solution, and a potassium bicarbonate aqueous solution, and the mass concentration of the neutralizing agent is 5-20%.

2. A liquid crystal spinning method for heterocyclic aramid fibers according to claim 1, characterized in that: In step S2, the mass fraction of the heterocyclic aramid polymer in the liquid crystal spinning solution is 15-35%, and the temperature of the liquid crystal spinning solution is 80-90°C.

3. A liquid crystal spinning method for heterocyclic aramid fibers according to claim 1, characterized in that: During the spinning process of step S2, the air layer height of the liquid crystal spinning solution passing through the spinneret is 3-15 mm.

4. A liquid crystal spinning method for heterocyclic aramid fibers according to claim 1, characterized in that: During the coagulation molding in step S2, the coagulation bath used is a sulfuric acid aqueous solution with a mass concentration of 10-30%, and the temperature of the coagulation bath is 20-30°C; In the water washing process of step S2, the water washing bath used is pure deionized water, and the water washing bath temperature is 20-40°C.

5. The liquid crystal spinning method of heterocyclic aramid fiber according to claim 1, characterized in that: In step S2, the temperature of the neutralizing agent is 20-40°C.

6. A liquid crystal spinning method for heterocyclic aramid fibers according to claim 1, characterized in that: The total draft ratio of the dry-jet wet spinning is 6.0 to 8.0 times.

7. A liquid crystal spinning method for heterocyclic aramid fibers according to claim 1, characterized in that: The molar ratio of the diamine monomer to the third monomer is 1:(0.5-3.5); the ratio of the total molar amount of the diamine monomer and the third monomer to the total molar amount of the terephthaloyl chloride is 1:(0.98-1.05); The weight of the first batch of terephthaloyl chloride added is 40-50% of the total amount of terephthaloyl chloride added; the weight of the second batch of terephthaloyl chloride added is 50-60% of the total amount of terephthaloyl chloride added.

8. The liquid crystal spinning method of heterocyclic aramid fiber according to claim 1, characterized in that: The substituted p-phenylenediamine monomer is selected from any one of the following structures: 。

Citation Information

Patent Citations

  • Aramid fiber containing fluorine and preparation method thereof

    CN101781813B

  • Preparation method of high-tensile high-model heterocycle aramid fiber

    CN101787582B

  • High-performance heterocyclic aramid fiber as well as preparation and application thereof

    CN101921395B

  • A high-performance heterocyclic aramid containing chlorine, its preparation method and application

    CN104357939B

  • A high-strength and high-modulus heterocyclic aramid fiber and preparation method thereof

    CN115678004B